High porosity 3D printed titanium mesh allows better bone regeneration - Rui Ma; Qian Liu; Libo Zhou; Lingxiao Wang (BMC, 2023)
Abstract Background Most patients with insufficient bone mass suffer from severe horizontal or vertical bone defects in oral implant surgery. The purpose of this study was to compare the bone regeneration effects of titanium meshes with different porosity in the treatment of bone defects. Methods Nine beagle dogs were equally divided into three groups based on execution time. Three months after the extraction of the first to fourth premolars of the mandible, three bone defects were randomly made in the mandible. Bone particles and three kinds of three-dimensional (3D) printed titanium nets with different porosities (low porosity group (LP), 55%; medium porosity group (MP), 62%; and high porosity group (HP), 68%) were replanted in situ. The beagles were killed 4, 8, and 12 weeks after surgery. Formalin-fixed specimens were embedded in acrylic resin. The specimens were stained with micro-CT, basic fuchsin staining, and toluidine blue staining. Results Micro-CT analysis showed that the trabecular thickness, trabecular number, and bone volume fraction of the HP group were higher than those of the other two groups. Moreover, the trabecular separation of the HP group decreased slightly and was lower than that of the MP and LP groups. Histological staining analysis showed that the trabecular number in the HP group was higher than in the other two groups at 8 and 12 weeks, and the bone volume fraction of the HP was higher than that in the other two groups at 12 weeks. Moreover, the trabecular thickness of the MP was higher than that of the LP group at 12 weeks and the trabecular separation was lower in the HP group at 4 and 8 weeks. The differences were statistically significant (p < 0.05). Conclusion A 3D printed titanium mesh with HP in a certain range may have more advantages than a titanium mesh with LP in repairing large bone defects.